2022
DOI: 10.1002/adsc.202200677
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzofurans from Sulfur Ylides and ortho‐Hydroxy‐Functionalized Alkynes

Abstract: The synthesis of benzofurans from readily accessible sulfur ylides and ortho‐hydroxy aryl alkynes is reported. The transformation proceeds through an isomerization/nucleophilic addition/cyclization/aromatization cascade. The substrate scope is very general with respect to both reactants and the products are afforded in 43–94% yield under conditions which are catalyst‐free and additive‐free.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Catalyst-free synthesis has gained a valuable place in novel methodologies regarding the synthesis of benzofuran derivatives. Yu et al 108 reported the catalyst-free synthesis of benzofuran heterocycles 108 by successive reactions of hydroxyl-substituted aryl alkynes 106 and sulfur ylides 107 which included the formation of isomers followed by the addition of nucleophile to generate intermediate B . The subsequent cyclization of intermediate B then led to the formation of an aromatic ring.…”
Section: Precedented Approachesmentioning
confidence: 99%
“…Catalyst-free synthesis has gained a valuable place in novel methodologies regarding the synthesis of benzofuran derivatives. Yu et al 108 reported the catalyst-free synthesis of benzofuran heterocycles 108 by successive reactions of hydroxyl-substituted aryl alkynes 106 and sulfur ylides 107 which included the formation of isomers followed by the addition of nucleophile to generate intermediate B . The subsequent cyclization of intermediate B then led to the formation of an aromatic ring.…”
Section: Precedented Approachesmentioning
confidence: 99%
“…Since the pioneering work developed by Johnson, Corey and Chaykovsky in the 1960s, namely the Johnson–Corey–Chaykovsky reaction, 7 sulfur ylides could now be used as C1, C2, and C3 synthons in various cascade annulation reactions, providing many strategies to synthesize structurally diverse carbo- and hetero-cyclic compounds. 8 The research groups of Aggarwal, 9 Tang, 10 Xiao, 11 Huang 12 and others 13 have disclosed many elegant reactions of sulfur ylides used to generate novel compounds. As part of our ongoing research program on methods to synthesize carbo- and hetero-cycles, 14 we report an efficient synthesis of 2,3-disubstituted indolines that relies on metal-free [4 + 1] cycloaddition of sulfur ylides and o -sulfonamido aldimine (Fig.…”
mentioning
confidence: 99%